'Let's move:' a systematic review of spouse-involved interventions to promote physical activity. Issue 1 (2nd January 2018) - Richards, Elizabeth A.; Franks, Melissa M.; McDonough, Meghan H.; Porter, Kimberly
Abstract: Introduction : Physical inactivity elevates risk of chronic conditions and all-cause mortality. Given that health behavior changes often co-occur within couples, spouse-involved physical activity interventions have the potential to increase and maintain physical activity behavior of both partners. The purpose of this systematic review was to synthesize studies of physical activity interventions that include both partners in marital dyads to determine whether and how active involvement of both partners shapes the physical activity behavior change process.Methods : Randomized trials ( N  = 6) published through June 2017 were included in this systematic review under the following conditions: (1) both partners were directly involved in the intervention treatment group(s); (2) couples were randomly assigned to study conditions; and (3) physical activity or exercise was assessed as a primary outcome.Results : The six trials included 783 couples, with mean ages ranging from 27 to 71 years. These studies of couples and physical activity change were guided by established socio-behavioral perspectives and used a variety of strategies to promote behavior change. Overall, each of these studies demonstrated improvement in physical activity behavior, though improvements in physical activity did not differ consistently between intervention and comparison groups and sometimes were short-lived.Discussions : This systematic review provides initial support, albeit limited, that spouse-involved interventions can be effective in increasing physical activity. Addressing the needs and behavior change of both partners has the potential to increase effectiveness of couple-focused approaches to promote physical activity initiation and maintenance.